Efficacy and safety of biosimilar trastuzumab (HLX02) in patients with HER2-positive advanced breast cancer: a retrospective real-world analysis - Ye, Xuan; Wang, Linlin; Liu, Wensheng; Wang, Mengmeng; Guo, Zihan; Shan, Han; Zhai, Qing; Du, Qiong (Frontiers in Oncology, 2025)
BackgroundHLX02 is the first China-manufactured trastuzumab biosimilar. Few data are currently available about HLX02 in clinical practice. This study was designed to evaluate the real-world safety and efficacy of HLX02 in patients with HER2-positive metastatic breast cancer (MBC), as well as assessed the effectiveness of switching from trastuzumab originator (Herceptin®) to HLX02 during treatment.MethodsBetween April 2021 and October 2022, all patients with HER-2-positive MBC who received at least one cycle of HLX02 at Fudan University Shanghai Cancer Center were included in a retrospective analysis. Patients were divided into two groups: the naïve group (patients treated with HLX02 from the beginning) and the switched group (patients who switched from Herceptin® to HLX02). Efficacy evaluation and adverse events were compared between the two groups.ResultsA total of 124 eligible patients were finally included, with 80 patients (64.5%) in the naïve group, 44 patients (35.5%) in the switched group. The follow-up ranged from 0.7 to 40.2 months, the effectiveness rates were 57.5% in the naïve group and 54.5% in the switched group, respectively (P=0.751). The estimated median progression-free survival (PFS) were 13.70 (95% CI: 8.634–18.766) months and 14.70 (95% CI: 6.684–22.716) months in the naive and switched groups, respectively (P=0.192). Multivariate cox regression analysis suggested that brain metastasis and the current number of treatment lines were independent predictors of MBC PFS. Compared with first-line treatment, second-line treatment and third- or later-line treatment increased the disease risk by 2.095 times (95% CI: 1.043-4.210, P=0.038) and 3.035 times (95% CI:1.751-5.262, P<0.001), respectively. The incidence and distribution of treatment-emergent adverse events (TEAEs) occurrence between the two groups were relatively similar, with no significant statistical difference.ConclusionsHLX02 demonstrated favorable efficacy and safety in real-world practice comparable to those observed in previous HLX02 studies. Switching between trastuzumab originator and biosimilar for MBC treatment had no impact on efficacy and did not increase safety risks.